How much do you really like it: social networking sites' effectiveness as a communication channel for brands - Langaro, Daniela (2015)
The current research was motivated by the increasing brand adoption of Social Networking Sites, like Facebook in companies´ communication plans, combined with the few existing evidences towards their specific consequences for brands. Envisioning this research opportunity, the author has proposed a conceptual model focused on evaluating the impact of brand page participation (BPP) on users´ future brand intentions, through the mediating influences of brand knowledge and brand relationship constructs. The proposed model has originated three studies. The first study explores the effects of Social Networking Sites (SNS) on brand knowledge. The second study evaluates the effectiveness of SNS as a relationship channel for consumer product goods. The third study investigates the relative importance of brand knowledge and brand relationship constructs on influencing users future intentions to recommend the brand. A qualitative phase, with 10 individual interviews, was followed by a quantitative phase structured in two online surveys, with 203 and 575 valid responses obtained among Facebook users of brand like pages from consumer product goods. Confirmatory factor analyses were used to estimate the measurement models and structural equation modelling was used to test the proposed research hypotheses. Overall, the results confirm a positive and significant impact of SNS on users´ future intentions. This effect is mainly influenced by the impact of BPP on generating trust and awareness, thus influencing users´ affective commitment and brand attitude. Moreover, the thesis also proposes and validates the construct of BPP, positioning it as the key measure to be pursued when evaluating brands´ performances in SNS.